Ismaili history and intellectual traditions - Daftary, Farhad, author.
1 online resource
Keywords: The Ismailis represent an important Shi'i Muslim community with rich intellectual and literary traditions. The complex history of the Ismailis dates back to the second/eighth century when they separated from other Shi'i groups under the leadership of their own imams. Soon afterwards, the Ismailis organised a dynamic, revolutionary movement, known as the da?wa or mission, for uprooting the Sunni regime of the Abbasids and establishing a new Shi'i caliphate headed by the Ismaili imam. By the end of the third/ninth century, the Ismaili ds, operating secretly on behalf of the movement, were active in almost every region of the Muslim world, from Central Asia and Persia to Yemen, Egypt and the Maghrib. This book brings together a collection of the best works from Farhad Daftary, one of the foremost authorities in the field. The studies cover a range of specialised topics related to Ismaili history, historiography, institutions, theology, law and philosophy, amongst other intellectual traditions elaborated by the Ismailis. The collation of these invaluable studies into one book will be of great interest to the Ismaili community as well to anyone studying Islam in general, or Shi'i Islam in particular.